Evaluation of citations of Russian publications in the world patent documents - L. A. Tsvetkova (Ekonomika Nauki)
According to the European patent agency, 15% of the references in the patent search reports are so-called non-patent literature (NPL), which refer to scientific publications not related to the patents. An included overview of research proves that a high level of NPL citation indicates a research intensity of technical solutions proposed by the patent. There has been evaluated the level of citation of Russian scientific publications, indexed in Scopus, in patent documents with cross-country comparisons. It has shown by the indicator «number of citations of national publications patents» Russian Federation is almost 87 times inferior to the United States and more than ten times worse than the performance of Japan, China, and Germany. The indicator «number of citations in patents per 1,000 publications» for Russia is (4,9) less than for Turkish (5,4), Argentine (8,5), Mexican (7,0) and South African publications (7,6). Publications of Qatar, Saudi Arabia, and Egypt also have a substantially higher value of this indicator: with 8,0 to 15,3 and 9,5, respectively.